2016
DOI: 10.1108/lodj-09-2013-0124
|View full text |Cite
|
Sign up to set email alerts
|

The double-edged sword of helping behavior in leader-follower dyads

Abstract: Purpose – The purpose of this paper is to examine potential consequences of helping behaviors on leader and follower relationship satisfaction and transformational leadership (TFL) ratings. It is argued that follower helping behaviors can violate leaders’ and followers’ expectations of each other, and especially disadvantage male leaders because of gender-role stereotypes. Design/methodology/approach – Two studies were conducted. In Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 136 publications
1
21
0
Order By: Relevance
“…The relatively sparse attention to this topic is somewhat surprising, in light of the widespread recognition that even if positive feelings about organizational functioning can be a source of energy that prompts positive work activities (Karriker and Williams, 2009;Quinn et al, 2012;Wei, 2012), such energy allocations also might be challenging and compromise employees' ability to fulfil their formal job tasks (Bergeron, 2007;Koopman et al, 2016). That is, the allocation of positive personal energy resources to voluntary behaviours that help co-workers with their jobs can be indirectly rewarding for employees-by generating personal fulfilment and possible reciprocation by the targets of these behaviours (Hoption, 2016;Hui et al, 2000)-but these discretionary activities also might undermine their abilities to meet prescribed job duties (Bolino et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relatively sparse attention to this topic is somewhat surprising, in light of the widespread recognition that even if positive feelings about organizational functioning can be a source of energy that prompts positive work activities (Karriker and Williams, 2009;Quinn et al, 2012;Wei, 2012), such energy allocations also might be challenging and compromise employees' ability to fulfil their formal job tasks (Bergeron, 2007;Koopman et al, 2016). That is, the allocation of positive personal energy resources to voluntary behaviours that help co-workers with their jobs can be indirectly rewarding for employees-by generating personal fulfilment and possible reciprocation by the targets of these behaviours (Hoption, 2016;Hui et al, 2000)-but these discretionary activities also might undermine their abilities to meet prescribed job duties (Bolino et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This study has some shortcomings, which suggest research opportunities. First, the investigation centres on how job satisfaction spurs helping behaviour, instead of the reverse process whereby undertaking helping behaviours may be a source of satisfaction for employees: when employees believe that they can make a difference and assist their colleagues in becoming more successful, their excitement about these contributions could make them feel happier about their work situation (Hoption, 2016;Organ, 1988). Beyond the time lag of three weeks between the assessment of the predictor variable (job satisfaction) and dependent variable (helping behaviour), longitudinal research designs could explicitly investigate the long-term, causal processes that connect higher levels of job satisfaction with helping behaviours.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Helping behavior contributes to not only peer performance but also organizational effectiveness and employees' own well-being. To the extent that employees engage in such behaviors, they enhance the quantity and quality of peer performance (Podsakoff, Ahearne, & MacKenzie, 1997), improve group performance (Bachrach, Powell, Collins, & Richey, 2006), increase the organization's competitive advantage (Borman & Motowidlo, 1993), and enjoy higher levels of relationship satisfaction for themselves (Hoption, 2016). Moreover, the tendency to be a "good soldier" (Peloza & Hassay, 2006) and voluntarily reach out to other organizational members to help them complete their job tasks has an important ethical component, in that the notion of being "good" stems from employees' values and ethics (Turnispeed, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Each of these conceptions of followership implicitly and explicitly includes behaviors, skills, and traits of the follower that are determinants of leader–follower effectiveness. For example, in a study of 61 workplace dyads, helpfulness by a follower was found to improve their leader's relationship satisfaction (Hoption, ), while in a survey of food service workers, emotional intelligence of followers was found to positively impact job performance (Sy, Tram, & O'Hara, ). Inasmuch as helpfulness or emotional intelligence can be learned, it is reasonable to posit that followership can be developed.…”
Section: Followership In Humansmentioning
confidence: 99%